Gherao - Banerjee, Gobinda Lall (Calcutta, 1969)
Interest in 'Gherao' continues unabated. Such incidents reached its peak during the first United Front Ministry in 1967 but it became fewer during Dr. Ghosh's Ministry and the Governor's Rule. It is again occurring at the rate of one per day according to newspaper report. When confronted with these reports the present Labour Minister said on March 26, 1969 that in contrast with the days of the previous U.F. Government, Gheraos were not proving to be a problem this time. The Chief Minister also said on March 12, 1969 that Gherao in his opinion would not be a major problem in the state. On February 26, 1969, the Deputy Chief Minister said that they wanted production to im prove and did not want work to stop. These are good words no doubt and points to a change in policy but on the 3rd. of March, 1969, Alipore Police Magistrate had to pass orders upon the officer-in charge of Ballygunge Police Station to rescue the manager of a factory who along with his staff were gheraoed by workers inside the factory; obviously, inspite of the High Court Judgment the Police did not act at the first instance. This was exactly what happened with the Hare Street Police Station when the Chief Magistrate had to pass orders.
Keywords: Labour economics